Cities and Climate Change : Responding to an Urgent Agenda. - Group, World Bank (World Bank, 2011)
This volume comprises a collection of papers prepared and presented at the World Bank's Fifth Urban Research Symposium, as part of the World Bank Group's strategy to share and encourage research oriented to urban issues and bridge these academic results with the pressing needs of developing cities. The selected papers included in this book combine robust analytical pieces and theoretical insights with best practices from around the world. Specific case studies include New Orleans in the context of a fragile environment, a framework to include poverty aspects in the cities and climate change di.